2019
DOI: 10.4102/sajp.v75i1.1314
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on self-management education campaigns for back pain

Abstract: BackgroundEvidence-based clinical practice guidelines on back pain recommend early management and use of approaches that emphasise self-management, psychological and physical therapies. Lately, mass media campaigns, addressing misconceptions about back pain, have been conducted in developed countries.ObjectivesThis study retrieved and synthesised the contents of back pain messages and described the outcomes and effectiveness of the media campaigns.MethodSeventeen key words and 10 electronic databases were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This includes increasing patients' awareness of their functioning problems, collaborative decision-making regarding rehabilitation goals and interventions, and active engagement in their treatment even where rehabilitation professionals may be absent, for example, through self-management strategies. Patient awareness campaigns can be conducted regularly to promote contextualized rehabilitation-related educational messages effectively [ 53 ]. Patients will thus have better knowledge about the causes and treatment of their functioning problems and be better informed about where to get help.…”
Section: Discussionmentioning
confidence: 99%
“…This includes increasing patients' awareness of their functioning problems, collaborative decision-making regarding rehabilitation goals and interventions, and active engagement in their treatment even where rehabilitation professionals may be absent, for example, through self-management strategies. Patient awareness campaigns can be conducted regularly to promote contextualized rehabilitation-related educational messages effectively [ 53 ]. Patients will thus have better knowledge about the causes and treatment of their functioning problems and be better informed about where to get help.…”
Section: Discussionmentioning
confidence: 99%
“…Mass media campaigns have been used to influence clinician and patient beliefs by promoting a variety of public health messages including physical activity, smoking cessation, and sexual health (Stead et al., 2019). Two recent systematic reviews show that mass media campaigns can effectively alter public (Nkhata et al., 2019; Suman et al., 2021) and clinician beliefs about LBP and its management (Suman et al., 2021). In particular, the latter review found evidence that media campaigns can influence beliefs about the use of imaging in LBP management.…”
Section: Discussionmentioning
confidence: 99%
“…The campaign content included evidence-based messages that had been used in similar published campaigns. A systematic review of similar campaigns (Nkhata et al 2019) was conducted and the evidence-based messages for back pain were extracted. The evidence-based messages were then cross-culturally validated and prioritised.…”
Section: Campaign Messagesmentioning
confidence: 99%
“…Our study was designed based on evidence from previous back campaign messages (Nkhata et al 2019), as well as context-specific information. The feedback on the campaign was overwhelmingly positive.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation